PENGEMBANGAN LKPD MATEMATIKA BERBASIS GROUP INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Sisri Ananda Putri; Nana Sepriyanti; Rivdya Eliza (Universitas Islam Negeri Imam Bonjol Padang, 2022)
From the results of observations at MTsN 10 Padang Pariaman, it is known that students need LKPD that facilitates their mathematical communication skills. The required LKPD needs to be supported by an appropriate learning model. The Group Investigation model was chosen because it fits the characteristics of the problems in MTsN 10 and is suitable for collaboration with LKPD. This study aims to produce LKPD based on the Group Investigation model to improve valid, practical and effective mathematical communication skills. This research is a development research conducted with reference to the first 3 stages of the 4D model with the following stages: (1) define, (2) design, (3) develop. Practical trials were conducted on 12 students of MTsN 10 Padang Pariaman. The results of this study indicate that the developed mathematics worksheets meet the valid criteria with an average value of 84.9%. The developed math worksheets meet the practical criteria with an average score of 87.3% for educators and 84.6% for students. The developed math worksheets also meet the effective criteria with an average score of 88%. The effectiveness of the development of LKPD based on Group investigation is seen based on the completeness of the results of the Mathematical Communication Ability test that came from 12 students. Based on these results, it can be concluded that the development of LKPD based on the Group Investigation model is in the valid, practical, and effective categories so that it is suitable for use in the learning process and can improve students' mathematical communication skills. Educators can consider using this Group Investigation-based LKPD to improve the quality of mathematics learning in the classroom.